EXPERIMENTAL ANALYSIS OF THE MECHANICAL BEHAVIOR OF CLAY-CEMENT BLOCKS REINFORCED WITH COCONUT FIBERS - CONAND HONORÉ KOUAKOU; MORO OLIVIER BOFFOUE; ANGE CHRISTINE DJOHORE; KOFFI CLÉMENT KOUADIO; EDJIKÉMÉ EMERUWA (Journal of Engineering Studies and Research)
This article aims for analyzing under an axial stress, the behavior of earth blocks reinforced by various proportions of coconut fibers. For this fact, compressive and flexural tests were carried out after 28 days of maturation, on dry blocks elaborate with clay stabilized at 8% of cement and containing 0 to 1% of fibers 30 mm length. The experimental results show that the incorporation of fibers in the blocks improves their mechanical characteristics, increases their ductile deformation and delays their cracking. The best mechanical resistances are obtained at 0.8% of fibers because at this content, the distance between fibers is optimal.